Retinal vasculopathy with cerebral leukoencephalopathy with TREX1 mutation: a rare entity with a new mutation - Michela Giacoma Pin; Lucia Corrado; Gionata Strigaro; Andrea Bianco; Mattia Bellan; Claudio Musetti; Letizia Mazzini; Roberto Cantello; Sandra D’Alfonso; Domizia Vecchio (Rare)
Retinal vasculopathy with cerebral leukoencephalopathy and systemic manifestations (RVCL-S) is a rare autosomal dominant vasculopathy caused by heterozygous C-terminal truncating mutations in three-prime repair exonuclease (TREX1) gene. The clinical spectrum includes vascular retinopathy, focal brain dysfunctions and other systemic manifestations, including Raynaud phenomenon, anemia with gastrointestinal bleeding, hypothyroidism and liver and kidney diseases. We report the case of a 46-year-old Italian man with RVCL-S, initially misdiagnosed as glioma or cerebral lymphoma. The patient presented with a 5-day history of mild ideo-motor slowdown, subacute mild left hemiparesis and dysarthric speech. Brain magnetic resonance imaging (MRI) showed a right temporo-insular large lesion with surrounding edema and inhomogeneous enhancement. One month later he presented focal motor seizures to his left side with subsequent generalization. He repeated a brain MRI showing a dimensional increase of the lesion (restricted at diffusion weighted imaging and enhanced peripherally). Medical history included microvascular liver disease, microvascular kidney disease, anemia, and scleroderma with Raynaud’s phenomenon. On oral steroids, a third brain MRI demonstrated volumetric reduction of the lesion with small nodular enhancement. Considering the pseudotumoral brain onset and the multisystemic involvement, RVCL-S was suspected and genetic analysis confirmed the presence of the new heterozygous mutation p.S267Qfs*57 in the C-terminal of the TREX1 gene.